Variation in risk seeking behavior in a natural experiment on large losses induced by a natural disaster - Lionel Page; David A. Savage; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2012)
This study explores people's risk attitudes after having suffered large real-world losses following a natural disaster. Using the margins of the 2011 Australian oods (Brisbane) as a natural experimental setting, we find that homeowners who were victims of the floods and face large losses in property values are 50% more likely to opt for a risky gamble - a scratch card giving a small chance of a large gain (500,000) - than for a sure amount of comparable value (10). This finding is consistent with prospect theory predictions of the adoption of a risk-seeking attitude after a loss.
Keywords: D03; D81; C93; 330; Decision under risk; large losses; natural experiment